2016
DOI: 10.1136/bmj.i5813
|View full text |Cite
|
Sign up to set email alerts
|

Community acquired pneumonia incidence before and after proton pump inhibitor prescription: population based study

Abstract: Objective To examine the risk of community acquired pneumonia before and after prescription of proton pump inhibitor (PPI) and assess whether unmeasured confounding explains this association.Design Cohort study and self controlled case series.Setting Clinical Practice Research Datalink (1990 to 2013) in UK.Participants Adult patients with a new prescription for a PPI individually matched with controls.Main outcome measures Association of community acquired pneumonia with PPI prescription estimated by three met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 32 publications
(39 reference statements)
6
50
1
2
Order By: Relevance
“…An interesting finding of this study was the association between acid‐suppressive therapy and MDRO pneumonia. The role of proton‐pump inhibitor therapy in contributing to pneumonia has been documented previously . The findings of this study expand on previous findings by suggesting that acid‐suppressive therapy is an independent predictor of pneumonia due to an MDRO.…”
Section: Discussionsupporting
confidence: 86%
“…An interesting finding of this study was the association between acid‐suppressive therapy and MDRO pneumonia. The role of proton‐pump inhibitor therapy in contributing to pneumonia has been documented previously . The findings of this study expand on previous findings by suggesting that acid‐suppressive therapy is an independent predictor of pneumonia due to an MDRO.…”
Section: Discussionsupporting
confidence: 86%
“…Second, to study hyperkalemia impact in a subcohort more likely to have chronic HF, and thus be more closely followed up, patients who were alive at 6 months after HF discharge had an echocardiography performed and were treated with both ARBs or ACEis and β blocker up to this date were separately examined. Third, as an alternative method to account for remaining unmeasured confounding when comparing outcomes in patients with and without hyperkalemia with HF, the ratio of the 2 matched HRs observed after versus before the hyperkalemia/index date (ie, the prior event rate ratio adjusted rate ratio) was estimated . This method is based on the assumption that differences in outcomes between hyperkalemia‐exposed and matched hyperkalemia‐unexposed patients present already before experiencing hyperkalemia reflect the combined effect of remaining unmeasured confounders, independent of any effect of hyperkalemia.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies, including meta‐analyses, have reported high risk of pneumonia soon after PPI therapy initiation, although negative associations have also been reported . A recent observational study of the first year after PPI prescription used the prior event rate ratio (PERR), which adjusts differences in postprescription pneumonia incidence between cases and controls with preexisting differences to correct for unmeasured confounding. That study used data from individuals in primary care in England and found that pneumonia rates increased during the first 30 days of PPI prescription (incidence rate ratio (IRR)=1.19, 95% confidence interval (CI)=1.14–1.25), but pneumonia rates were even higher during the 30 days immediately before the first PPI prescription (IRR=1.92, 95% CI=1.84–2.00), perhaps because the greater medical scrutiny of individuals with pneumonia led to more PPI prescribing for comorbidities, including medications commonly co‐prescribed with PPIs.…”
mentioning
confidence: 99%